2011
DOI: 10.1016/j.jns.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Parkinson's disease: More than just disinhibition

Abstract: In the last few years it has become clear that impulsivity is a complex behaviour composed of different domains and dependent on different neural networks. The proposed pathogenetic mechanisms for the emergence of impulsivity disorders in Parkinson's Disease (PD) can be broadly separated into three potentially interacting processes: the contribution of premorbid susceptibility to impulsivity, the contribution of the disease itself to the behaviour and the potential contribution of therapeutic agents. Growing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 95 publications
(121 reference statements)
2
31
1
1
Order By: Relevance
“…In these patients, the correlation analysis revealed that our medicated patients with higher k ‐values (i.e., more impulsive) had less rCBF changes in “reward‐areas” as compared to the less impulsive patients (i.e., lower k ‐value). Thus, from our observations, it appears obvious that failure of inhibition and impulsivity incorporates a number of dissociable components [Antonelli et al, ; Chamberlain and Sahakian, ]. One component is related to the ability of processing decision‐making information useful to make a proper choice.…”
Section: Discussionmentioning
confidence: 80%
“…In these patients, the correlation analysis revealed that our medicated patients with higher k ‐values (i.e., more impulsive) had less rCBF changes in “reward‐areas” as compared to the less impulsive patients (i.e., lower k ‐value). Thus, from our observations, it appears obvious that failure of inhibition and impulsivity incorporates a number of dissociable components [Antonelli et al, ; Chamberlain and Sahakian, ]. One component is related to the ability of processing decision‐making information useful to make a proper choice.…”
Section: Discussionmentioning
confidence: 80%
“…As a consequence, movement initiation disorders are not easily alleviated by standard therapies [4][5][6]. Even worse, they can be aggravated by the treatments, for example worsened akinesia [7] or induced impulsivity [8][9][10]. A prerequisite for current therapeutic strategies is to understand the complexity of the basic mechanisms involved in movement initiation and related dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…However, "impulsivity" is a complex and multifaceted construct; Antonelli et al (2011) distinguished between cognitive impulsivity-which is characterized by altered decision-making (e.g. risk-taking, altered time-perception, and avoidance of waiting) and motor impulsivity-which is associated with a relative inability to inhibit prepotent responses.…”
Section: Introductionmentioning
confidence: 99%